UASOS: An Experimental Environment For Assessing Mental Fatigue & Cognitive Flexibility During Drone Operations - Hinss, Marcel F.; Maria Vitale, Vincenzo; Phan, Nhat Tien; Roy, Raphaelle N.; Brock, Anke M. (2024 19th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2024)
Mental fatigue from continuous operations without breaks represents a safety issue for military drone operations, as these systems are complex and operate during long shifts. Military operations are hard to study due to their sensitive nature. The open-access program UASOS serves as a testbed to examine the effects of mental fatigue in an ecologically valid environment. UASOS recreates fundamental aspects of military drone operations in a controllable environment that is easy enough for novices to understand but demanding enough to elicit mental fatigue. Participants alternate between navigating a drone-using either a trackball/mouse or a joystick-and searching for visual targets. The protocol is set up in a way that taxes the cognitive flexibility of participants by constantly requiring them to alternate between tasks. In addition, several parameters such as difficulty, duration, questionnaires, training phases, and more can be adapted. The task also allows for synchronization with physiological data using LabStreamingLayer. Implemented in python, the code is set up to be easily installed.CCS CONCEPTS* Human-centered computing → Interactive systems and tools; Laboratory experiments; * Applied computing → Military.